1968
DOI: 10.1070/rc1968v037n07abeh001662
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Complexones

Abstract: Organophosphorus complexones represent a new class of multidentate reagents. The paper gives a broad survey of methods for the preparation of aminoalkylphosphonic acids, which include the organophosphorus complexones, and their complexing and biological properties are described. The specific characteristics of these complexones are revealed with respect both to certain elements-beryllium, the rare-earth metals, heavy elements, etc.-and with respect to extending the pH range of complex formation. The mode of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Zobiole et al (2010a) reported that A, gs and E were reduced by glyphosate, possibly due to direct damage by glyphosate to chloroplasts (Campbell et al 1976;Pihakaski and Pihakaski 1980;Nilsson 1985) or immobilization of Mg and Mn required for chlorophyll formation and photosynthesis. Since glyphosate is a glyphosate a strong metal chelator (Jaworski 1972;Kabachnik et al 1974;Coutinho and Mazo 2005), it may immobilize essential micronutrients required as components, co-factors or regula- (Johal and Huber 2009). According to Cakmak (Cakmak et al 2009), the period for the observed 'yellow flashing' is most likely dependent on the ability of the plants to recover through adequate root uptake of the specific elements that are immobilized by glyphosate in plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zobiole et al (2010a) reported that A, gs and E were reduced by glyphosate, possibly due to direct damage by glyphosate to chloroplasts (Campbell et al 1976;Pihakaski and Pihakaski 1980;Nilsson 1985) or immobilization of Mg and Mn required for chlorophyll formation and photosynthesis. Since glyphosate is a glyphosate a strong metal chelator (Jaworski 1972;Kabachnik et al 1974;Coutinho and Mazo 2005), it may immobilize essential micronutrients required as components, co-factors or regula- (Johal and Huber 2009). According to Cakmak (Cakmak et al 2009), the period for the observed 'yellow flashing' is most likely dependent on the ability of the plants to recover through adequate root uptake of the specific elements that are immobilized by glyphosate in plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that glyphosate reduced shoot concentrations of mineral nutrients in RR soybean as compared to nontreated RR soybean or their near-isogenic nontreated non-RR with the effect being most pronounced in the early maturity group cultivars (Zobiole et al 2010a). The effect on decreased shoot mineral concentration could be attributed to reductions in photosynthetic parameters as a result of direct damage of glyphosate to chlorophyll (Pihakaski and Pihakaski 1980;Kitchen et al 1981;Reddy et al 2004) or immobilization of essential micronutrients by glyphosate, due to the ability of glyphosate to form insoluble glyphosatemetal complexes (Jaworski 1972;Kabachnik et al 1974;Bromilow et al 1993;Coutinho and Mazo 2005).…”
Section: Introductionmentioning
confidence: 95%
“…A series of the new lipophilic ␣-aminophosphonates containing various substituents, R 1 , R 2 , R 3 and R 4 , were synthesized by the Kabachnik-Fields reaction [6] in 62-95% yields.…”
Section: Resultsmentioning
confidence: 99%
“…Suggestions about the structures of low-molecular-weight aminophosphonic acid-metal complexes on the basis of potentiometric measurements, NMR, and IR investigations have been reported by a number of groups [34][35][36][37][38]. Taking these results into consideration, elucidation of the structures of the polymer-metal complexes described in this paper should be possible.…”
Section: Investigations Of the Complex Structurementioning
confidence: 94%